Characterization and simulation of liquid phase exfoliated graphene-based films for heat spreading applications. (September 2016) - Zhang, Yong; Edwards, Michael; Samani, Majid Kabiri; Logothetis, Nikolaos; Ye, Lilei; Fu, Yifeng; Jeppson, Kjell; Liu, Johan
Abstract: This paper concerns the thermal properties of graphene-based films for heat spreading applications. Following liquid phase exfoliation (LPE) films were made by two different methods, vacuum filtration and drop coating. Temperature decreases of up to 6 °C and 4 °C were measured at a heat flux density of 1200 W/cm 2 for the vacuum filtrated and drop coated films respectively. For the first time in this paper, three different methods were combined to evaluate and predict the thermal performance of such graphene-based films. Resistance thermometers were used to monitor the hotspot temperature decrease versus the Joule heat flow as a result of using graphene-based heat spreaders. The 3ω method was used to experimentally determine the in-plane and through-plane thermal conductivities of such films. A finite element model of the hotspot test structure was setup using the in-plane and through-plane thermal conductivities (110 and 0.25 W/mK, respectively) obtained from the 3ω measurements. Simulations were performed to predict the hotspot temperature decrease with excellent agreement obtained between all methods. The results indicate that the alignment and purity of the graphene-based films, as well as their thermal boundary resistance with respect to the chip, are key parameters when determining the thermal performance of graphene-based heat spreaders.